2021
DOI: 10.1186/s12884-021-04230-5
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence as a predictor of antenatal care services utilization in Rwanda

Abstract: Background Although compelling evidence shows that exposure to intimate partner violence (IPV) during pregnancy is detrimental to both physical and mental health of the victims and their fetuses, studies on negative impact of IPV on antenatal care (ANC) services utilization are scarce. Methods The aim of the current study was to determine the impact of IPV exposure on ANC services utilization indicators such as (i) initiation of care within the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
4
8
0
Order By: Relevance
“…These were pregnancy wantedness (planned, when pregnancy was wanted at the time of occurrence or unplanned when pregnancy was not wanted at all or not wanted at the time of occurrence) and spousal violence during pregnancy (experienced or not experienced). The two variables have been identified as having significant predictive power on antenatal care utilization [49][50][51][52]. Two external environmental factors, namely, place of residence and geo-political zone were included for statistical control.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…These were pregnancy wantedness (planned, when pregnancy was wanted at the time of occurrence or unplanned when pregnancy was not wanted at all or not wanted at the time of occurrence) and spousal violence during pregnancy (experienced or not experienced). The two variables have been identified as having significant predictive power on antenatal care utilization [49][50][51][52]. Two external environmental factors, namely, place of residence and geo-political zone were included for statistical control.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…Intimate partner violence is considered as a public health and human rights issue. Prior research has shown that women who experienced physical or sexual intimate partner violence have a risk of developing physical problems [3][4][5], including difficulty accessing and using antenatal care services for pregnant women [6], as well as mental health issues such as depression, anxiety, posttraumatic stress disorder, suicide, and alcohol abuse [4].…”
Section: Introductionmentioning
confidence: 99%
“…Women who experience intimate partner violence are less likely to have control over their reproductive health (i.e., access to contraception and/or protection, forced pregnancy or forced termination, etc. ), less likely to have access to ANC, especially early initiation of ANC, and are at higher risk for STIs, mental health disorders, and adverse birth outcomes ( 86 , 102 106 ). At the most extreme end of intimate partner violence, homicide is a leading cause of death amongst pregnant women and women of reproductive age in the US ( 106 , 107 ).…”
Section: Promoting Reproductive Health To Improve Population Healthmentioning
confidence: 99%